Multi-instrument observations of SCIPS: 1. ISR and GPS TEC results. (February 2021) - Dinsmore, Ross; Mathews, J.D.; Coster, Anthea; Robinson, R.M.; Sarkhel, Sumanta; Erickson, Philip J.; Urbina, Julio
Abstract: An uninterrupted multi-day (6–8 May 2013) ionospheric F-region event with features indicative of medium-scale traveling ionospheric disturbances (MSTIDs) was detected with the Millstone Hill (MH) incoherent scatter radar (ISR). It was later identified, with the addition of Global Positioning System total electron content (GPS-TEC) imaging, as a novel ionospheric phenomenon. This phenomenon is herein termed semi-coherent ionospheric pulsing structures (SCIPS). The presumptive-MSTIDs in this multi-day event had a ~1 h period and were observed during calm-to-minor geomagnetic conditions using both the vertical-looking (Zenith) and steerable (Millstone Hill Steerable Antenna, or MISA) MH ISR systems. To image the MH MSTID events on a larger horizontal scale than is possible with ISR systems alone, a dense network of GPS TEC receivers was leveraged. The ISR-observed event was located in the GPS-TEC data geographically centered on the MH location with a ~100 km resolution (pixel size). However, keogram analysis of the GPS-TEC data revealed that the event had coherency across the continental United States. The same technique additionally exposed similar events occurring globally throughout the observing period. Our multi-instrument approach allows us to conclude that the event was comprised of large-scale and continuously forced, semi-coherent ionospheric pulsing structures (SCIPS) that masqueraded as MSTIDs when viewed locally. The GPS-TEC images show that the SCIPS were stationary in longitude on a global scale, but appeared to propagate in a southward direction in the Northern Hemisphere. It was not possible to obtain direct imaging in the southern hemisphere due to the smaller number of receivers. The SCIPS appear to originate at high latitudes and, in several instances, were coherent across over 10, 000 km. The apparent high latitude source location, ubiquity, and large-scale coherence of the SCIPS suggest unexpected impulsive auroral oval sources containing enough energy to continually force the observed MSTID-like structures even during low geomagnetic activity periods. Highlights: Incoherent scatter radar (ISR) and GPS total electron content (TEC) reinterpret traveling ionospheric disturbances (TIDs). Multi-day medium-scale TIDs (MSTIDs) reclassified as global semi-coherent ionospheric pulsing structures (SCIPS). ISR and GPS-TEC allow local through global imaging of SCIPS. SCIPS have southward propagation, large scale coherency (10, 000 km), and long-term ubiquity. SCIPS' features suggest impulsive auroral oval sources even during low geomagnetic activity.